MANAJEMEN DAN KOMUNIKASI HINDU PADA PELAKSANAAN RITUAL PARUMAN BARONG DI PURA LUHUR NATAR SARI, DESA APUAN, KABUPATEN TABANAN, BALI - nyoman bontot (Satya Sastraharing : Jurnal Manajemen, 2020)
The barong meeting ritual is one of the peak processions of the many series of piodalan ageng in Luhur Natar Sari Temple. Barong meeting ritual involves a lot of resources and participants, both Hindu people in sekala (real) and Ratu Gede (barong) in niskala. The large number of resources and parties involved in the barong meeting ritual requires adequate management and communication systems. The implementation of the barong meeting ritual is based on the existence of ideology (theology, politics, and economics) and the belief of Hindu people supporters of the ceremony. For the success and smooth implementation of the ceremony, implementing management (Bali royal era, Indonesia independence era, and global era). For the sake of smooth coordination and implementation of the entire procession, implementing Hindu communication (vertical and horizontal), verbal dan non-verbal, oral and written, and using communication facilities such as mobile phones, loudspeakers, and radio communications (handy talkie).